Pengaruh Pengetahuan Akuntansi Dan Pengalaman Berwirausaha Terhadap Penggunaan Informasi Akuntansi Pelaku Usaha Mikro Kecil Dan Menengah Di Kecamatan Cikarang Barat - Euis Ratnasari; Adi Suprayoga; Fathullah Fathullah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Micro, Small and Medium Enterprises (MSMEs) play an important role in economic growth in Indonesia. Accounting knowledge is a knowledge that is used to study all financial income and expenditure activities of MSME actors. Entrepreneurial experience is a lesson that has been learned as long as entrepreneurs start their business. Entrepreneurial experience is one of the reasons to develop knowledge about accounting. The sample of this research is 100 SMEs in West Cikarang District. Data collection in this study used a questionnaire as a research instrument. The results of the study indicate that (1) There is a positive influence of Accounting Knowledge on the Use of Accounting Information. This is evidenced by the value of t_count > t_table (2.701 > 1.985) and a significance value of 0.008<0.05. (2) There is a positive influence of Entrepreneurial Experience on the Use of Accounting Information. This is evidenced by the value of t_count > t_table ( 3,678 > 1,985) and a significance value of 0.000 < 0.05. (3) There is a joint influence of Accounting Knowledge and Entrepreneurial Experience on the Use of Accounting Information. This is evidenced by the value of f_count 19.598 > f_table3.09 with a significant probability of 0.000 <0.05.